Organic synthesis using (diacetoxyiodo)benzene (DIB): Unexpected and novel oxidation of 3-oxo-butanamides to 2,2-dihalo-N-phenylacetamides - Liu, Wei-Bing; Chen, Cui; Zhang, Qing; Zhu, Zhi-Bo (Beilstein Journal of Organic Chemistry, 2012)
A novel and reliable method for the direct preparation of 2,2-dihalo-N-phenylacetamides is reported. The key transformation involves the cleavage of a carbon–carbon bond in the presence of DIB and a Lewis acid as the halogen source, and thus this method significantly expands the value of DIB as a unique and powerful tool in chemical synthesis. This protocol not only adds a new aspect to reactions that use other hypervalent iodine reagents but also provides a wide space for the synthesis of disubstituted acetamides.
Keywords: cleavage of carbon–carbon bond; (diacetoxyiodo)benzene; difunctionalized acetamides; novel oxidation; 3-oxo-N-phenylbutanamides